Temporal changes in the burden of leukaemia and lymphoma in the Australasia and Oceania regions, 2010–2019: an analysis of the Global Burden of Disease Study 2019 - Lan Gao; Peter Lee; Thi Quynh Anh Ho (BMJ Open)
Objectives Leukaemias and lymphomas are among the most prevalent and significant cancers in Australasia and Oceania. This study aims to examine the burden of leukaemias/lymphomas and its temporal trend in Australasia and Oceania from 2010 to 2019.Design Epidemiological studyMethods Data from the Global Burden of Disease (GBD) 2019 were used to examine the burden of leukaemia/lymphoma key subtypes (acute lymphocytic leukaemia (ALL), acute myeloid leukaemia (AML), chronic lymphocytic leukaemia (CLL), chronic myeloid leukaemia (CML), Hodgkin-lymphoma (HL) and non-Hodgkin’s lymphoma (NHL)) by sex and 5 year age groups (from <5 years to 85 years+), in terms of incidence, prevalence, disability-adjusted life years (DALYs) and deaths. Estimated average percentage changes were calculated to assess the temporal trends of leukaemia/lymphoma burden (incidence/prevalence/DALYs/deaths) from 2010 to 2019 in Australasia and Oceania.Results AML and NHL were the leading causes of leukaemia/lymphoma burden in both regions. Age-standardised rates (ASRs) for AML versus NHL in Australasia were: incidence 4.72 versus 19.06, DALYs 89.01 versus 161.68 and deaths 4.15 versus 8.02 per 100 000 population. ASRs for AML versus NHL in Oceania were: incidence 1.36 versus 1.08, DALYs 49.16 versus 38.30 and deaths 0.91 versus 0.98 per 100 000 population. From 2010 to 2019, Australasia observed an increasing trend in incidence/prevalence/deaths across most leukaemias/lymphomas and increasing/stable trend in DALYs for AML/CLL/NHL, while Oceania observed increasing trends in incidence/prevalence/DALYs for CLL/NHL and stable trends in all outcomes (except for prevalence (stable)) for AML. Contrasting mortality trends for ALL/CML/HL were observed between the two regions (increasing/stable in Australasia and decreasing in Oceania). Statistically significant differences were observed in disease burden trends between sexes, with males experiencing a greater increase (or smaller decrease) in the burden for AML in both regions.Conclusions Different temporal trends in leukaemia/lymphoma burden observed in two closely situated geographic regions with different sociodemographic indices highlight the necessity for region-specific intervention strategies to enhance the access to innovative disease treatments, reducing leukaemia/lymphoma burden.